Voices from the Field: Investigating the Emergent Form of an Indigenous Dance Movement Therapy Training Program in South Africa - Vivien Speiser (Creative Arts in Education and Therapy, 2023)
The article describes the author’s involvement in the development of an innovative academic dance movement therapy (DMT) training program during her Fulbright Senior Scholar assignments in Johannesburg, South Africa, spanning from the early 2020 to her subsequent return in 2023. It highlights the challenges posed by the COVID-19 pandemic and emphasizes the author’s dedication to engaging with key interested parties and some of the significant voices in the fields of dance and movement education, community work, training, and therapy in South Africa. Situated within the Drama for Life program at the University of the Witwatersrand, this article explores the author’s goal of participating in the dialogue about the crafting of an Afro-centric training program in DMT. This program is designed to integrate existing practices and forms in dance movement and performance with cultural and spiritual elements, incorporating multiple histories, and including indigenous knowledge systems to inspire, and to integrate some of these perspectives and collaborative opportunities within the program design.